Classification of three dimensional complex Leibniz algebras - Rikhsiboev, Ikrom M.; Sattarovich, Rakhimov Isamiddin (American Institute of Physics, 2011)
The aim of this paper is to complete the classification of three-dimensional complex Leibniz algebras. The description of isomorphism classes of three-dimensional complex Leibniz algebras has been given by Ayupov and Omirov in 1999. However, we found that this list has a little redundancy. In this paper we apply a method which is more elegant and it gives the precise list of isomorphism classes of these algebras.We compare our list with that of Ayupov-Omirov and show the corrections which should be made.